Dinamika Partai Nahdlatul Ulama pada Pemilihan Umum 1955 di Jawa Barat - budi sujati (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2020)
The first Islamic Congress in Cirebon in 1922 was one of the seeds of opposition between Reformers and Traditionalists. This was followed by a compilation of two camps which were agreed to hold the Masyumi Party as a symbol of the unity of the Muslims. However, in reality, there was a successful conflict between the Traditionalist and Reformist camps so that the Traditional camp represented by NU was canceled by the Masyumi ties by holding the 19th NU Conference in Palembang 1952. This had implications for the existence of the NU Party in West Java to invoke its hegemony. together with Masyumi so that in the 1955 general election the NU Party only voted under Masyumi, PNI and PKI. This paper will explain how the dynamics faced by the West Java Nahdlatul Ulama when jamiyah changed course became a political party that had implications for the existence of the West Java NU Party before the election took place or afterwards. This research is descriptive with a qualitative methodology. The use of this method is to be able to explain a phenomenon that occurs in the Nahdlatul Ulama organization as a result of becoming a Political Party by using a Politological approach through the stages of Heuristics, Criticism, Interpretation and Historiography.